Mas Cotek (Ficus deltoidea): a possible supplement for Type II Diabetes: (a pilot study) - Draman, Samsul; Md Aris, Mohd Aznan; Mohd Rus, Razman; Akter, Seikh Farid Uddin; Halim, Noor Azlina; A. Rahman, Nor Azlina; Khattak, Muhammad Muzaffar Ali Khan; Hazali, Norazlanshah; Mohd Hassan, Norazian (Forest Research Institute Malaysia, 2011)
The aim of this research was to study the effect of the Ficus deltoidea (Mas Cotek) leaves on fasting blood sugar, renal and lipid profile of Type II diabetic patients. This study was carried out at Polyclinic Balok, located in Kuantan, Pahang, Malaysia. Twenty patients participated in the study and they were divided into two (2) groups of ten (10) patients each. The inclusion criteria were registered as diabetic patients in the health centre, diagnosed as type II diabetes mellitus for more than one (1) year, age 18 years and above, HbA1c more than 6.5% and have contactable telephone number. The patients in the intervention group has been given F. deltoidea 350 mg twice daily orally and monitored every 20 days for two (2) months. In conclusion, the effects on fasting blood sugar, HbA1C, renal and lipid profiles were not significant. The patients in the intervention group felt energetic and fresh compared to the control.